The Role of the World Meteorological Organization (WMO) in Mitigating Natural Disasters in Laos 2024 Through the Climate Risk and Early Warning Systems (CREWS) Program - Finna Kharisma Marulitta; Gonda Yumitro (Journal of International Relations Diponegoro, 2026)
Developing countries face significant challenges in managing climate-related disaster risks due to limitations in technical capacity, institutional frameworks, and early warning systems. Laos is one of the countries with high vulnerability to hydrometeorological disasters, particularly floods. The World Meteorological Organization (WMO) is an international organization that plays a crucial role in enhancing the capacity of developing nations to address climate-related disaster risks through technical assistance, early warning systems, and institutional strengthening. One of its flagship programs, the Climate Risk and Early Warning Systems (CREWS), is designed to assist high-risk countries in developing impact-based early warning systems. This study aims to analyze the role of WMO through the CREWS program in disaster mitigation efforts in Laos, using the 2024 major flood as a case study. The research adopts a descriptive qualitative approach and is analyzed through the theoretical framework of the role of international organizations from a liberalist perspective as proposed by Kelly-Kate S. Pease, specifically focusing on the roles of problem solver, capacity builder, and aid provider. The method involves a literature study approach, with data collected from books, journals, internet sources, and other written references as the foundation for the analysis. The findings reveal that prior to the intervention, Laos faced significant limitations in infrastructure, risk data, and inter-agency coordination. Through the CREWS program, WMO contributed to strengthening the technical capacity of the Department of Meteorology and Hydrology (DMH) of Laos, modernizing weather stations, and implementing an impact-based forecasting approach. This study finds that WMO's intervention through CREWS has encouraged improved disaster preparedness and response at both national and community levels, although challenges remain in system integration and funding sustainability. The research underscores the importance of multilateral cooperation and strengthened climate risk governance in enhancing the resilience of developing countries to disasters.